The Role of CYP2B6*6 Gene Polymorphisms in 3,5,6-Trichloro-2-pyridinol Levels as a Biomarker of Chlorpyrifos Toxicity Among Indonesian Farmers - Jen Fuk Liem; Dwi A. Suryandari; Safarina G. Malik; Muchtaruddin Mansyur; Dewi S. Soemarko; Aria Kekalih; Imam Subekti; Franciscus D. Suyatna; Bertha Pangaribuan (Korean Society for Preventive Medicine, 2022)
Objectives One of the most widely used pesticides today is chlorpyrifos (CPF). Cytochrome P450 (CYP)2B6, the most prominent catalyst in CPF bioactivation, is highly polymorphic. The objective of our study was to evaluate the role of CYP2B6*6, which contains both 516G>T and 785A>G polymorphisms, in CPF toxicity, as represented by the concentration of 3,5,6-trichloro-2-pyridinol (TCPy), among vegetable farmers in Central Java, Indonesia, where CPF has been commonly used. Methods A cross-sectional study was conducted among 132 vegetable farmers. Individual socio-demographic and occupational characteristics, as determinants of TCPy levels, were obtained using a structured interviewer-administered questionnaire and subsequently used to estimate the cumulative exposure level (CEL). TCPy levels were detected with liquid chromatography-mass spectrometry. CYP2B6*6 gene polymorphisms were analyzed using a TaqMan® SNP Genotyping Assay and Sanger sequencing. Linear regression analysis was performed to analyze the association between TCPy, as a biomarker of CPF exposure, and its determinants. Results The prevalence of CYP2B6*6 polymorphisms was 31% for *1/*1, 51% for *1/*6, and 18% for *6/*6. TCPy concentrations were higher among participants with CYP2B6*1/*1 than among those with *1/*6 or *6/*6 genotypes. CYP2B6*6 gene polymorphisms, smoking, CEL, body mass index, and spraying time were retained in the final linear regression model as determinants of TCPy. Conclusions The results suggest that CYP2B6*6 gene polymorphisms may play an important role in influencing susceptibility to CPF exposure. CYP2B6*6 gene polymorphisms together with CEL, smoking habits, body mass index, and spraying time were the determinants of urinary TCPy concentrations, as a biomarker of CPF toxicity.